2013
DOI: 10.1634/theoncologist.2012-0340
|View full text |Cite
|
Sign up to set email alerts
|

Case Control Study of Women Treated With Chemotherapy for Breast Cancer During Pregnancy as Compared With Nonpregnant Patients With Breast Cancer

Abstract: Background. The purpose of this analysis was to compare disease-free survival (DFS), progression-free survival (PFS), and overall survival (OS) between pregnant and nonpregnant patients with breast cancer. Methods. From 1989 to 2009, 75 women were treated with chemotherapy during pregnancy. Each pregnant case was matched on age and cancer stage to two nonpregnant patients with breast cancer (controls). Fisher's exact test, the Kaplan-Meier method, and Cox proportional hazards regression models were used. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 22 publications
(19 reference statements)
1
42
1
2
Order By: Relevance
“…In contrast to our findings, two recent studies have shown that pregnant breast cancer patients do not have poorer prognosis (Amant et al 2013, Litton et al 2013. The discussion of this topic is beyond the scope of this manuscript; however, we believe that several factors could explain these contradicting results including the limitations of the case-control design, differences in identifying matching controls, lack of statistical power, and different treatment strategies.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, two recent studies have shown that pregnant breast cancer patients do not have poorer prognosis (Amant et al 2013, Litton et al 2013. The discussion of this topic is beyond the scope of this manuscript; however, we believe that several factors could explain these contradicting results including the limitations of the case-control design, differences in identifying matching controls, lack of statistical power, and different treatment strategies.…”
contrasting
confidence: 99%
“…Recently, several groups including ours have published on the prognosis of patients diagnosed with breast cancer during pregnancy (Azim et al 2012b, Amant et al 2013, Litton et al 2013. Results of these studies have witnessed major controversy with studies showing worse outcomes, while others showing no difference in prognosis or even improved survival.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is not advised anymore, but if breast cancer is diagnosed in the early stage of gestation, cessation of pregnancy may become a more viable choice considering the risks associated with a delay in standard treatment [39]. In general, the fiveyear survival rate in PABC is similar to the non-pregnant population; however, two primary risk factors which may affect the survival rate of PABC are a history of recent pregnancy and delay in treatment for 3 to 6 months [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…After adjustments for age, stage, grade, hormone receptor status, HER-2 status, histology, type of chemotherapy, use of trastuzumab, radiotherapy, and hormone therapy no significant difference between the groups was detected (6). In another study of 75 women receiving chemotherapy during PABCa, matched for age and cancer stage with two nonpregnant patients, a better five-year overall survival (OS) was detected; 77% (95% CI: 63.9%-86.4%) for pregnant patients and 71% (95% CI: 61.1%-78.3%) for controls (7). However, a study of 65 patients where PABCa patients were stage-matched with two non-pregnant controls concluded a poorer disease free survival (DFS) of PABCa (HR 2.3; 95% CI: 1.3-4.2) compared to the non-pregnant controls (9).…”
Section: Breast Cancer During Pregnancymentioning
confidence: 99%
“…Diagnosis of breast cancer in the postpartum period was associated with significantly poorer outcome (pooled hazard ratio (pHR) 1.85; 95% CI: 1.28-2.65) compared with diagnosis during pregnancy (pHR 1.29; 95% CI: 0.74-2.24) (5). However, the data from the literature is inconsistent and several cohort studies have shown that after adjustment to prognostic factors, pregnancy per se does not affect the disease-free or overall survival (6)(7)(8). Similar overall survival of PABCa was found in a multicenter registry study where 311 women diagnosed with breast cancer during pregnancy were identified and compared with 865 non-pregnant women (6).…”
Section: Breast Cancer During Pregnancymentioning
confidence: 99%